Spielt die Aderhautdicke beim idiopathischen Makulaforamen eine Rolle? - Schaal, Karen; Marx, Stefanie; Dithmar, Stefan (Der Ophthalmologe, 2012)
Background:The pathogenesis of idiopathic macular hole (MH) formation is not fully understood and the choroid might be involved in its etiology. Recently published data reported choroidal thickness (CT) to be significantly thinner in eyes with idiopathic MH and in fellow eyes compared to age-matched healthy controls [24].MethodsThe enhanced depth imaging (EDI) modus of the Spectralis OCT (Heidelberg Engineering, Heidelberg) was used to measure subfoveal CT in 12 patients with MH of which 2 suffered from bilateral MH. Measurements were manually acquired preoperatively using the horizontal foveal scan of the 7-line scan (5 × 30 perifoveal) with 100 averaged scans per scan, between the outer border of the retinal pigment epithelium and the inner scleral border. Additional CT measurements were obtained 8 weeks and 6 months postoperatively.ResultsSubfoveal CT of the 12 patients with MH (10 ♀, 2 ♂; 68 ± 7 years) was 274 ± 65 µm. The CT of the 10 patients with healthy fellow eyes measured 268 ± 75 µm and CT of the 2 patients with bilateral MH measured 309 ± 34 µm in the non-operated eye. The mean axial length (AL) in eyes with MH was 23.64 ± 0.59 mm and in healthy fellow eyes 23.68 ± 0.54 mm. After surgery MH closure was obvious in all eyes, the postoperative CT at 8 weeks measured 284 ± 77 µm and at 6 months 276 ± 73 µm.ConclusionsThe EDI-OCT procedure enables measurements of CT. In the patients studied a reduced CT could not be found neither in patients with macular holes nor in the fellow eyes. There was no significant change in CT comparing preoperative with postoperative measurements. In contrast to recently published data [24] no reduction in CT in idiopathic macular hole could be demonstrated.